Fluorescence labelling and self-healing microcapsules for detection and repair of surface microcracks in cement matrix. (1st March 2020) - Wang, Xingang; Chen, Zhongfa; Xu, Wei; Wang, Xingjing
Abstract: Fluorescence labelling and self-healing microcapsules (FLSM) with fluorescein sodium labelled epoxy resin as core materials and urea-formaldehyde resin as shell materials were synthesized by in situ polymerization via ultrasonic dispersion. Micromorphology, chemical structure, thermal stability and reactivity of FLSM were studied by ESEM, FTIR, TGA and DSC. Laser scanning confocal microscopy (LSCM) was served to characterize the surface microcracks repair process of cement paste mixed FLSM. The results showed that FLSM with full spherical particles and a certain roughness on the surface were well dispersed in the range of 150–300 μm of particle size. The addition of fluorescein sodium has no significant effect on the micromorphology, chemical structure, thermal stability and reactivity of FLSM. After being cut by the blade, the fluorescence width of FLSM increased from 9 μm to 22 μm within 0–12 h. The core materials of FLSM was basically lost, which indicated that the core materials had good fluidity. When the microcracks occur on the surface of cement paste, FLSM can not only detect the specific location of the microcracks and repair them, but also infer the width of the microcracks. It provides a new method for detecting and repairing microcracks on the surface of cement matrix. Graphical abstract: Image 1 Highlights: Fluorescence labelling and self-healing microcapsules were synthesized by in situ polymerization via ultrasonic dispersion. The surface microcracks were characterized and the repair process was investigated by laser scanning confocal microscopy. Fluorescence labelling and self-healing microcapsules can detect and repair the surface microcracks in cement matirx.